Kontribusi Kepemimpinan Pelayan Kepala Sekolah, Budaya Sekolah, Komitmen Guru dan Partisipasi Orang Tua terhadap Pengembangan Literasi - N.W. Pirgianti; K.R. Dantes; B.R. Werang (Pascasarjana Universitas Pendidikan Ganesha, 2023)
The study aims to determine the contribution of the principal’s servant leadership, school culture, teacher commitment and parental participation to the development of literacy capabilities of students of SMP Negeri 6 Nusa Penida . This type of research is classified as ex post facto with descriptive and correlational research. The study used a saturated sampling technique in which all members of the population, totally 83 students of grade VIII, were used as samples (census). Data collection method is using a questionnaire. Data were analyzed using descriptive techniques and regression tests. The results of the research : ((1) there was a partially significant contribution between the principal’s servant leadership to the literacy development of students with effective contribution 24,09%. (2) there was a partially significant contribution between school culture to the literacy development of students with effective contribution 15,96%. (3) there was a partially significant contribution between teacher commitment to the literacy development of students with effective contribution 21,24%. (4) there was a partially significant contribution between parental participation to the literacy development of students with effective contribution 11,67%. (5) there was a significant contribution simultaneously between the principal’s servant leadership, school culture, teacher commitment and parental participation to the literacy development of students with determination 0,729 and give effective contribution about 72,96 %. It means that about 72,96% these independent variables have a significant contribution simultaneously to the dependent variable.